3-Gene-TB-SCORE Accuracy for Tuberculosis Disease Diagnosis Is Not Affected by Immune-Mediated Inflammatory Disease Comorbidity - Petruccioli, Elisa; Alonzi, Tonino; Navarra, Assunta; Altera, Anna Maria Gerarda; Cuzzi, Gilda; Farroni, Chiara; Repele, Federica; Gualano, Gina; Lindestam Arlehamn, Cecilia S.; Palmieri, Fabrizio; Salmi, Andrea; Vanini, Valentina; et al. (International journal of molecular sciences, 2025)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a major global health threat. Approximately one-quarter of the world’s population has an Mtb-specific immune response and are classified as having tuberculosis infection (TBI), with a lifelong 5–10% risk of developing TB disease. This risk is elevated in individuals with immune-mediated inflammatory diseases (IMID) undergoing immunosuppressive therapies. To evaluate the diagnostic accuracy of the 3-gene TB-SCORE for TB disease in individuals within the TB spectrum, including those with TBI-IMID in a low TB endemic country, we prospectively enrolled 104 individuals with TB, TBI, TBI-IMID, and healthy donors. The 3-gene TB-SCORE and Mtb-specific response were evaluated and correlated with the participant’s clinical status. Patients with TB disease showed a significantly lower TB-SCORE compared to other cohorts. ROC analysis showed moderate diagnostic accuracy for TB disease (AUC 0.70–0.71). TB-SCORE was unaffected by IMID status or timing of Mtb exposure. Mtb-specific CD4+ T cells had no correlation to TB-SCORE. This is the first evaluation of TB-SCORE as a diagnostic tool for TB disease in a low-endemic setting. While further validation is needed, our findings support its potential as a biomarker for TB disease, even in complex clinical settings involving IMID.